2016
DOI: 10.1111/dme.13265
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels are not a contributing factor to higher prevalence of depressive symptoms in people with Type 2 diabetes mellitus: the Hoorn study

Abstract: The study found no evidence that low vitamin D levels are a contributing factor to higher depression scores in people with Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In Paper III, we found an inverse association between serum 25(OH)D3 and poor mental health at baseline, but not at follow-up on mental well-being after four years. The finding that vitamin D was associated with mental health at baseline is in line with one (140) of the two previous studies confined to populations with diabetes (140,141). We found no association between serum 25(OH)D3 and vitality at baseline, and the association first seen at follow-up disappeared after controlling for data regarding diabetes status and lifestyle factors.…”
Section: Patients With Type 2 Diabetes (Papers II and Iii)supporting
confidence: 92%
“…In Paper III, we found an inverse association between serum 25(OH)D3 and poor mental health at baseline, but not at follow-up on mental well-being after four years. The finding that vitamin D was associated with mental health at baseline is in line with one (140) of the two previous studies confined to populations with diabetes (140,141). We found no association between serum 25(OH)D3 and vitality at baseline, and the association first seen at follow-up disappeared after controlling for data regarding diabetes status and lifestyle factors.…”
Section: Patients With Type 2 Diabetes (Papers II and Iii)supporting
confidence: 92%
“…We found only one retrospective study [34] published in 2019, which indicates that VDD may predict poor cognitive performance in patients with T2DM. VDD has been recently correlated with depression, although a crosssectional study [35] published in 2017 concerning elderly with T2DM concluded that VDD appeared not to be a contributing factor to higher depression scores in elderly with T2DM. Although, a cross-sectional study conducted in 2015 [36] showed that VD sufficiency is associated with higher self-reported diabetes treatment satisfaction and better diabetes-specific quality of life in elderly with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D levels were lower in the depression group than in the control group. In contrast, Westra et al 15 found no correlation between vitamin D deficiency and the risk of depression in patients with T2DM. Other studies have shown different vitamin D levels in patients with obesity experiencing depression compared with those without depression.…”
Section: Discussionmentioning
confidence: 90%
“…Patients with type 2 diabetes mellitus (T2DM) are at risk for depression, with a higher prevalence rate (11)(12)(13)(14)(15)(16)(17).6%) than the general population (3-4%). 1,2 Furthermore, 41% of patients with T2DM experience depression.…”
mentioning
confidence: 99%